Notary Criminal Responsibility In Terms of Notary Workers Doing Criminal Following Letters - Oktadevi Nurfildzah; Moh Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Writing this journal aims to analyze and examine how accountability notary in the case of workers committed the crime of forgery. In Article 1, paragraph 1 of Law notary mention that Notary Public Officials authorized to make authentic act and have more authority as referred to this Act or under another Act. Notary otherwise authorized by the attribution of the State through Law Notary. That is, authority attached to office of notary. Carrying out his duties as well as the Notary Public in general assisted by Notary workers. In terms of preparing everything what is needed in the manufacture of an authentic deed. One of the documents tobe prepared by notary public workers is letter. Notary workers only be assistance in carrying out his job. Responsibility for authentic act remains the responsibility of notary. If the workers notary committed the crime of forgery that resulted his disability certificate is authentic, then it possible the notary must responsible. Forgery that can occur because the fake letter, fake powers and authority of the contents of the letter. Forms Criminal Liability Notary notary worker if proof acriminal act of forgery is acriminal participation in the crime of forgery contained in Article 55 Juncto Article 263 paragraph 1 and (2) Penal Code or Article 264 or Article 266 of the Criminal Code, and Article 56 paragraph 1 and Article 263 paragraph 1,2 Penal Code or Article 264 or 266 of the Criminal Code. Because Notary considered negligent in carrying out his duties as well.